Peran Literasi Keuangan dalam Memoderasi Pengaruh Praktik Akuntansi terhadap Akurasi Laporan Keuangan UMKM - Mirah Lestari Ni Ketut; Komang Sri Widiantari (Economics and Digital Business Review, 2025)
This study aims to analyze the effect of recording quality, compliance with SAK EMKM, and account separation on the financial reporting accuracy of MSMEs, with financial literacy as a moderating variable. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to 180 respondents from coffee shop MSMEs in North Kuta District, Badung Regency, Bali. The results indicate that recording quality, SAK EMKM compliance, and account separation have a positive and significant impact on financial reporting accuracy. Financial literacy strengthens the relationship between recording quality and account separation with reporting accuracy, while its moderating effect on SAK EMKM compliance is marginal. The model explains 56% of the variance in financial reporting accuracy (R² = 0.56) with good predictive relevance (Q² = 0.38). The findings highlight that financial literacy is a crucial contingency factor enhancing the effectiveness of accounting practices among MSMEs. Improving financial literacy, along with training in SAK EMKM implementation and digital bookkeeping systems, is essential to strengthen the accuracy and accountability of MSME financial reports.